IMPACT OF PERCUTANEOUS TRANSLUMINAL RENAL ANGIOPLASTY ON LEFT VENTRICULAR MASS AND ITS RELATIONSHIP TO CARDIOVASCULAR OUTCOME IN HYPERTENSIVE PATIENTS WITH RENAL ARTERY STENOSIS. (April 2021) - Iwashima, Yoshio; Fukuda, Tetsuya; Horio, Takeshi; Kusunoki, Hiroshi; Hayashi, Shin-Ichiro; Kamide, Kei; Kawano, Yuhei; Yoshihara, Fumiki; Ishimitsu, Toshihiko
Abstract : Objective: Renal artery stenosis (RAS) is associated with secondary hypertension, which is often resistant to antihypertensive medication.The aim of the present study was to evaluate the impact of renal angioplastry on left ventricular (LV) mass, as measured by echocardiography, and further to determine whether LV mass reduction is associated with reduced rates of cardiovascular events in hypertensive patients with RAS. Design and method: A total of 144 hypertensive patients with RAS (mean age 69 years; 22.2% fibromuscular dysplasia [FMD]) who underwent angioplasty were included. Echocardiography was performed at baseline and after one year, and were thereafter followed up for a median of 5.6 years for the primary composite outcomes. The primary endpoint of this study was first occurrence of the composite of cardiovascular events including all-cause death, myocardial infarction, stroke, or adverse aortic event. Results: In both the FMD and atherosclerotic stenosis (ARAS) groups, LV mass decreased after angioplasty, but the decrease in LV mass index (-15.4 ± 18.3% versus -0.8 ± 27.8%, p < 0.01) as well as the regression rate of LV hypertrophy was greater in FMD. Multiple logistic regression analysis indicated that FMD (odds ratio [OR] 2.94, p < 0.01), severe RAS (greater than or equal to 90%) (OR 2.94, p < 0.05), and higher LV mass index at baseline (OR 2.94 for 1 standard deviation increase, p < 0.001) were independent predictors of LV mass index decrease of at least 20%. The primary composite outcomes occurred in 45 patients (31.3%). In FMD, lower LV mass index after one year (hazard ratio 2.81 for 1 standard deviation increase, p < 0.05) or regression of LV mass (hazard ratio 0.75 for 5% decrease, p = 0.054) showed a tendency to be associated with better outcomes; however, these associations were not found in ARAS. Conclusions: Hypertensive patients with ARAS have less regression of LV mass in response to angioplasty than those with FMD, and LV mass regression is less useful as a surrogate marker of outcomes especially in ARAS.